Food technology neophobia and animal ethics orientation: Influences on cultured meat acceptance in Croatia - Marija CERJAK; Ivica FALETAR (Journal of Central European Agriculture)
Although cultured meat is not yet widely available on the market, numerous scientific studies have already looked at consumers in relation to the purchase and consumption of this type of meat. However, many aspects of the consumer perspective on this meat are still unknown in many national markets. The aim of this study was to investigate the influence of attitudes towards novel food technologies and animal ethics orientation on the willingness to consume (WTC) cultured meat among Croatian consumers and to determine whether respondents differ in these attitudes. The results showed that attitudes measured with the food technology neophobia scale have a significant influence on WTC. The more positive the attitude towards the benefits of novel food technologies, the greater the willingness to consume cultured meat. In contrast, the more pronounced the attitude towards the risks and dangers of new food technologies, the less willing consumers are to consume cultured meat. The consumers for whom the positive aspects of new food technologies predominate tend to be those who have a more liberal world view than others. The animal ethics orientation had no significant influence on the WTC. The results obtained contribute to the extensive literature on the acceptance of cultured meat and can be used to develop a communication policy to promote cultured meat in the market studied.